Decorin as a possible strategy for the amelioration of COVID-19. (July 2021) - Allawadhi, Prince; Singh, Vishakha; Khurana, Isha; Rawat, Pushkar Singh; Renushe, Akshata Patangrao; Khurana, Amit; Navik, Umashanker; Allwadhi, Sachin; Kumar Karlapudi, Satish; Banothu, Anil Kumar; Bharani, Kala Kumar
Abstract: Coronavirus pandemic has emerged as an extraordinary healthcare crisis in modern times. The SARS-CoV-2 novel coronavirus has high transmission rate, is more aggressive and virulent in comparison to previously known coronaviruses. It primarily attacks the respiratory system by inducing cytokine storm that causes systemic inflammation and pulmonary fibrosis. Decorin is a pluripotent molecule belonging to a leucine rich proteoglycan group that exerts critical role in extracellular matrix (ECM) assembly and regulates cell growth, adhesion, proliferation, inflammation, and fibrogenesis. Interestingly, decorin has potent anti-inflammatory, cytokine inhibitory, and anti-fibrillogenesis effects which make it a potential drug candidate against the COVID-19 related complications especially in the context of lung fibrosis. Herein, we postulate that owing to its distinctive pharmacological actions and immunomodulatory effect, decorin can be a promising preclinical therapeutic agent for the therapy of COVID-19.